Saluran, Margin, Efisiensi dan Farmer’s Share Pemasaran Jamur Merang (Volvariella volvaceae) Kelompok Tani Rukun Makmur Desa Argorejo Kabupaten Bantul - Rohman, Moh. Ali Abdur; Salehawati, Nurul (Universitas Wiralodra, 2025)
The aimed of this study was to determine the marketing channel of merang mushrooms for the Rukun Makmur farmer group and to determine the cost, margin, farmer’s share and efficiency of the merang mushrooms marketing channel of the Rukun Makmur farmer group. The population taken from the supply chain research for merang mushrooms cultivation were farmers, traders, and final consumers who involved in the marketing channel of merang mushrooms in the Rukun Makmur Farmer Group. The method of taking respondents used the snowball sampling method. Data analysis in this study used three analyzes, there were: (1) descriptive, margin and marketing efficiency, and (3) farmer's share. The results of the research showed that the perpetrators of merang mushrooms marketing institutions in the Rukun Makmur farmer group were farmers, traders (central or non-central market traders), and consumers. There are 4 marketing channels for straw mushrooms in the Rukun Makmur farmer group: Marketing channel I straw mushroom farmers - consumers, marketing channel II straw mushroom farmers - local market traders - consumers, marketing channel III straw mushroom farmers - local market traders - retailers - consumers Marketing channel IV straw mushroom farmers - wholesale market traders - retailers - consumers. The marketing costs of 1 kilogram of straw mushrooms in this marketing channel include 0, Rp. 2,500, Rp. 3,500 and Rp. 2,500. The marketing margin in this study was 0, Rp. 6,000, Rp. 10,000, Rp. 8,000. The least marketing costs and margins were in channel I, the largest marketing costs and margins were in channel III. Marketing efficiency in this straw mushroom marketing channel was 0%, 6.9%, 8.75% and 6.57%. The results showed that all marketing channels were included in the efficient marketing category. The most efficient marketing channel was in channel I and the least efficient was in channel III. The results of the farmer's share analysis in this study were 100%, 83%, 75%, 79%. These results show that the share received by farmers is greater than that of consumers, so it can be said that all marketing channels are efficient.